Characterization of shape memory polymer - Teng, David Jia Wen (2019)
Shape memory materials are materials that can be deformed under certain conditions and return to its original shape and dimension after heating. This includes different type of material compositions such as metal alloy, polymers and hybrids. Shape memory materials have interesting properties and characteristics, each shape memory material memory has different parameters required for deformation and recovery. This project will study 3 different types of shape memory polymer, thermoplastic polyurethane filament, hard shape memory foam and vitrimers polyurethane. This includes the material recovery and surface topography. This project will also include the methods required for achieving sub-micron wrinkles on thermoplastic polyurethane filament by using surface etching.